Proposta de sistema embarcado para implementação da técnica biospeckle laser - Teixeira, Gabriel Ramos (2021)
The biospeckle laser is a technique whose effectiveness has already been proven in several experiments and research, proving to be a useful tool for the observation and analysis of non-invasive phenomena. However, due to its execution characteristics and sensitivity to the nature of the phenomena involved and the objects of study, the implementation and use of this technique are still challenging. To be executed, it needs a camera to capture the images of the analyzed structure and a computer to process them. In recent times, technological development has allowed the improvement of capture devices and computational systems, even allowing them to be presented in the form of structures with embedded hardware and software and with reduced dimensions. Some works have made use of these systems in order to present more portable approaches, with low cost and with dedicated use. Thus, this paper aimed to evaluate the feasibility of an embedded platform to develop a system capable of performing the acquisition, processing and analysis of the biospeckle laser, in order to meet the requirements and particularities of the technique.